2014
DOI: 10.1007/s10549-013-2824-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of CYLD downregulation in breast cancer

Abstract: Cylindromatosis (CYLD) is a tumor suppressor gene that is mutated in familial cylindromatosis, a rare autosomal dominant disorder associated with numerous benign skin adnexal tumors. CYLD is now known to regulate various signaling pathways, including transforming growth factor-β signaling, Wnt/β-catenin signaling, and NF-κB signaling by deubiquitinating upstream regulatory factors. Downregulation of CYLD has been reported in several malignancies; however, the clinical significance of CYLD expression in many ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
2
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 46 publications
1
65
2
3
Order By: Relevance
“…Most importantly we have demonstrated for the first time, that CYLD down-regulation enhances the ability of basal and luminal types of breast cancer cells to grow in an anchorage independent manner. Anchorageindependent growth is a hallmark of aggressive cancer cells and our findings are consistent with the correlation of patient poor prognosis with down-regulated CYLD expression (3).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Most importantly we have demonstrated for the first time, that CYLD down-regulation enhances the ability of basal and luminal types of breast cancer cells to grow in an anchorage independent manner. Anchorageindependent growth is a hallmark of aggressive cancer cells and our findings are consistent with the correlation of patient poor prognosis with down-regulated CYLD expression (3).…”
Section: Discussionsupporting
confidence: 90%
“…However, the causative role of CYLD down-regulation in the deregulation of homeostatic mechanisms of various cell types that lead to transformation has not been established. Previous studies have indicated that increased expression of CYLD in two basal-type breast cancer cell lines (BT-549 and MDA-MB-231) promotes their apoptosis whereas down-regulation of CYLD in MDA-MB-231 inhibits apoptosis and promotes cell migration (3,16,17). In the present study we demonstrated for the first time, that the direct growth and migratory-suppressive role of CYLD is also evident in a luminal type breast cancer cell line (MCF7) and an additional basal type breast cancer cell line (HCC1937).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CYLD has been revealed to play a central role in regulating various signaling pathways, including transforming growth factor-β, Wnt/β-catenin, c-Jun N-terminal kinase and nuclear factor-κB (NF-κB) signaling, and thus regulates the promotion of cancer development and progression (13)(14)(15)(16). Furthermore, the downregulation of CYLD has been reported in several malignancies (17)(18)(19)(20). Previous studies have revealed that CYLD expression is downregulated in breast cancer tissues compared with normal breast tissues (2,17).…”
Section: Introductionmentioning
confidence: 99%